Guzele Cafe / Kun Aqilah Marset ... [et al.] - Marset, Kun Aqilah; Basri, Nor Shafikah; Abdul Aziz, Aina Nasuha; Bacho, Noor Bahrina (2019)
Guzele Cafe is established as a partnership business between four people. The organization of Guzele Cafe consists of General Manager and Operational Manager which is Noor Bahrina Binti Bacho, Administrative Manager, Aina Nasuha Binti Abdul Aziz, Financial Manager , Nor Shafikah Binti Basri and Marketing Manager which is Kun Aqilah Binti Marset. Guzele has been chosen for the name of our business as in Turkish, Guzele means beautiful. Our authentic and relaxing cafe environment should make our customer increase day by day. Guzele Cafe is located at address, sublot 103, @ Aiman Mall Jalan Dato’ Mohd Musa, 94300, Kota Samarahan, Sarawak. The date of our commencement business is on 1st January 2020 and was launched at the mentioned address. Guzele Cafe is expected to attract customers with its delicious, refreshing cakes and sweet, also coffees. This business plan is to create a strong market position in Desa Ilmu, Kota Samarahan with the aid of help offour experienced people. We also focuses on meeting the customers demand regardless of ages, income range, ethnics and ethics in Kota Samarahan through our business.